Early drinking onset: A study of prevalence and determinants among 13‐year‐old adolescents in Norway. Issue 5 (28th July 2014) - Adolfsen, Frode; Strøm, Henriette Kyrrestad; Martinussen, Monica; Natvig, Henrik; Eisemann, Martin; Handegård, Bjørn Helge; Koposov, Roman
<x xml:space="preserve">Abstract</x> Early drinking onset is associated with different psychosocial adjustment problems among adolescents. The aim of this study was to assess determinants associated with early drinking and to identify factors predicting early drinking onset among adolescents. The study included 1, 550 eighth‐graders with a mean age of 13.5 years from 41 schools. A total of 24% (boys 29%, girls 19%) had ever drunk alcohol, while 14% had drunk some alcohol in the last 30 days. Further, early drinking was associated with gender, religion, school performance, smoking and bullying in the bivariate tests. Predictors of early drinking onset were identified by generalized linear mixed models with two multivariable models created. The first model included social and environmental variables. Entering intentions, expectancies, attitudes and norms into the multivariable analysis resulted in a significant improvement of the model fit constituting 86% in the second model. The percentage correctly classified those (56%) who had been drinking in the second model which was two times higher compared to the first model. Gender, religion and smoking emerged as significant predictors of drinking in both models.